Highly heterogeneous residual malaria risk in western Thailand. Issue 6 (May 2019) - Nguitragool, Wang; Karl, Stephan; White, Michael; Koepfli, Cristian; Felger, Ingrid; Singhasivanon, Pratap; Mueller, Ivo; Sattabongkot, Jetsumon
Graphical abstract: Highlights: There is a highly heterogenous risk of malaria infection among villagers in western Thailand. The molecular force of infection was determined in a low endemic setting. There is a strong correlation between malaria prevalence and the force of infection. Abstract: Over the past decades, the malaria burden in Thailand has substantially declined. Most infections now originate from the national border regions. In these areas, the prevalence of asymptomatic infections is still substantial and poses a challenge for the national malaria elimination program. To determine epidemiological parameters as well as risk factors for malaria infection in western Thailand, we carried out a cohort study in Kanchanaburi and Ratchaburi provinces on the Thailand-Myanmar border. Blood samples from 999 local participants were examined for malaria infection every 4 weeks between May 2013 and Jun 2014. Prevalence of Plasmodium falciparum and Plasmodium vivax was determined by quantitative PCR (qPCR) and showed a seasonal variation with values fluctuating from 1.7% to 4.2% for P. vivax and 0% to 1.3% for P. falciparum. Ninety percent of infections were asymptomatic. The annual molecular force of blood-stage infection (mol FOB) was estimated by microsatellite genotyping to be 0.24 new infections per person-year for P. vivax and 0.02 new infections per person-year for P. falciparum . The distribution of infections was heterogenous, that is, the vast majority of infections (>80%) were found in a small number of individuals (<8% of the study population) who tested positive at multiple timepoints. Significant risk factors were detected for P. vivax infections, including previous clinical malaria, occupation in agriculture and travel to Myanmar. In contrast, indoor residual spraying was associated with a protection from infection. These findings provide a recent landscape of malaria epidemiology and emphasize the importance of novel strategies to target asymptomatic and imported infections.